تطوير المواد الدراسية لمادة الإملاء للمرحلة الابتدائية الإسلامية في ضوء المدخل التحليلي - Farhalim Farhalim; Wildana Wargadinata; Nur Hasan Abdul Barry; Qaribullah Babikr Mustofa (Journal of Arabic Language Teaching, 2023)
Dictation lessons at this school are the additional material, but in the learning process, there are problems, such as the need for more basic books and measurement methods. This is what happens at school ibtidaiyah Al-Anwar Cangringrandu Perak Jombang dan sekolah ibtidaiyah Bahrul Ulum Tambak beras. This study aims to develop a textbook for Madrasah Ibtidaiyyah Al-Anwar and Ibtidaiyyah Bahrul Ulum Jombang to improve writing skills, especially in the field of Imla’ by paying attention to those aspects of knowledge that are needed. The problem of this study is; a form of textbook Imla’developed, The extent to which the effectiveness of Imla’ learning with using textbooks that have been developed. The type of research is the R & D Sugiyono and experiments using the Pree test and post-test on the experimental and control classes. Then to determine the level of effectiveness is the test-T. The results of this study are 1) the development of textbook material dictation for students of Madrasah Ibtidaiyyah Al-Anwar dan Madrasah Ibtidaiyyah Bahrul Ulum Jombang, 2) the development of textbooks that have been prepared, the learning process has increased effectiveness and efficiency. With a value of 16,190476 t count> t-table 3,65 with 99,9%. Confidence level. This means that there is a significant difference between the final value of the initial value. الدرس الاملاء في هذه المدرسة تدخل على المحتوى الاضافي، ولكن في عملية التعلم هناك مشاكل منها عدم الكتاب الأساسي و الطريقة و القياس. والهدف هذا البحث بتطوير المواد الدراسية لمادة الإملاء لتنمية مهارة الكتابة لدى طلاب المدرسة الابتدائية الانوار و مدرسة الابتدائية بحرالعلوم تمباك براس لدى طلاب وباهتمام كفاءة الطلاب واحتياجهم. يحتوي هذا البحث من ثلاثة مباحث: 1) تطوير الكتاب المواد الدراسية لمادة الإملاء على مدرسة الابتدائية الانوار جنكرينج راندو فيراك جومبانج و مدرسة الابتدائية بحرالعلوم تمباك براس جومبانج، 2) فعليه تعليم المواد الدراسية لمادة الإملاء باستخدام الكتابة المطور على مدرسة الابتدائية الانوار جنكرينج راندو فيراك جومبانج و مدرسة الابتدائية بحرالعلوم تمباك براس جومبانج. استخدم الباحث منهج البحث والتطوير بالنموذج الذي اقترحه سوغيونو. استخدم الباحث الاختبار القبلي والاختبار البعدي فى تطوير الكتاب التعليمي ولمعرفة فعالية الكتاب التعليمي. أما نتائج البحث: 1) إن التطوير حصل على الكتاب التعليمي فى مادة الإملاء فى المدرسة الابتدائية الانوار جنكرينج راندو فيراك جومبانج و مدرسة الابتدائية بحرالعلوم تمباك براس، 2) وتدل "ت" حساب 16،190476 أكبر من "ت" جدول 3,65 بجانب الصدق %99,9. هناك الاختلاف ذو معنى بين الاختبار القبلي والاختبار البعدي. والكتاب التعليمي فى مادة الإملاء فعال فى المدرسة الابتدائية الانوار جنكرينج راندو فيراك جومبانج و مدرسة الابتدائية بحرالعلوم تمباك براس جومبانج.